LEGAL PROTECTION FOR PERPETRATORS OF MINOR ENVIRONMENTAL CRIMES - Priska Deianeira Kulape; Amalia Syauket; Rama Dhianty (International Journal Labs, 2023)
Supreme Court Regulation Number 02 of 2012 concerning Adjustment of the Limits of Light Criminal Acts and the Amount of Fines was created with the intention of facilitating law enforcement, especially judges, to administer justice in the cases they adjudicate. However, in practice, restorative justice with ADR methods has not been optimally applied to light criminal acts. One of the areas with the most disparities is the issue of light criminal acts in the field of the environment. Therefore, this research aims to determine what constitutes light criminal acts in the field of the environment and to understand the legal protection for perpetrators of light criminal acts in the field of the environment. The research method used is a normative juridical method using secondary legal sources. The results of the study indicate the scope of light criminal acts in the field of the environment. Criminal acts regulated in Law Number 32 of 2009 concerning Environmental Protection and Management are specified in Articles 41 to 44 of Law Number 32 of 2009. If there is minor theft for environmental results, the Criminal Code must also be considered as the legal framework specifically regulating theft (lex specialis derogat legi generali). Legal protection for perpetrators of light criminal acts in the field of the environment must align with the goals of criminalization, with sociological, ideological, and juridical-philosophical approaches, based on the fundamental assumption that criminal acts disrupt the balance, harmony, and coherence in community life